Two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode and preparation method thereof
Through the design of two-dimensional MOFs/SnO2 quantum dots/MXene catalyst electrodes, the problems of poor catalytic activity and low reaction efficiency in electrocatalytic nitrogen fixation technology are solved, and efficient N2 reduction synthesis ammonia reaction is achieved, and multiple defects in the prior art are overcome.
Patent Information
- Application Number
- CN202411972391.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing electrocatalytic nitrogen fixing technology faces problems such as poor catalytic activity, excessive reaction potential, low solubility of N2 in aqueous solution, slow diffusion speed and easy deactivation of catalysts, which limits the conversion efficiency of electrocatalytic N2 reduction synthesis of ammonia.
A two-dimensional MOFs/SnO2 quantum dot/MXene catalyst electrode is adopted to make full use of the synergistic effects between the components through reasonable structural design, improve the conductivity and stability of the catalyst, and optimize the transmission path of reactants and the distribution of catalytic active sites.
Good catalytic activity and selectivity for N2 reduction synthesis ammonia reaction is achieved, reducing the reduction potential required for reduction, overcoming multiple defects in the existing electrocatalytic N2 reduction method, and achieving high-efficiency nitrogen reduction synthesis in normal temperature and pressure.
Smart Images

Figure CN119776904A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalyst electrodes, and more specifically, to a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode and a preparation method thereof. Background Art
[0002] Ammonia is not only a key raw material for fertilizer production, but is also widely used in the manufacturing process of explosives, plastics, dyes, refrigerants and other industries. The nitrogen (N2) content in the air is as high as 78%, which is an extremely abundant resource. However, due to the extremely high N≡N bond energy in the N2 molecule (about 941kJ mol -1 ), which makes its activation energy barrier extremely high and difficult to be directly converted into ammonia. Therefore, the development of efficient and energy-saving nitrogen conversion technology is of great significance to meet the growing demand for ammonia.
[0003] At present, the Haber-Bosch process is mainly used for industrial ammonia synthesis. This process uses iron-based catalysts to synthesize ammonia (NH3) from high-purity nitrogen (N2) and high-purity hydrogen (H2) under high temperature (over 300°C) and high pressure (over 100atm). Although the Haber-Bosch process has been widely used in industrial production, it has many disadvantages: harsh reaction conditions, high energy consumption and cost; at the same time, the process will emit a large amount of carbon dioxide (CO2) during the production process, causing environmental pollution.
[0004] As an emerging ammonia synthesis technology, electrocatalytic nitrogen fixation aims to use electricity under ambient conditions and water as a hydrogen source to directly reduce N2 to NH3. However, electrocatalytic nitrogen fixation technology still faces many challenges: poor catalytic activity, high reaction potential, low solubility of N2 in aqueous solution, slow diffusion rate, and easy deactivation of catalysts. These factors severely limit the conversion efficiency of electrocatalytic N2 reduction to synthesize ammonia.
[0005] Although metal-organic frameworks (MOFs) and SnO2 quantum dots have shown great potential in the field of catalysis, they still face many difficulties in the process of synthesizing ammonia.
[0006] For example, although two-dimensional (2D) MOFs nanosheets have advantages such as large aspect ratio and many exposed active sites, their poor conductivity limits their application in electrocatalysis. Although SnO2 quantum dots have large specific surface area, interface effect of nanoparticles and quantum size effect, how to effectively prevent their agglomeration and improve their dispersibility in composite materials is also a problem that needs to be solved urgently.
[0007] As an emerging two-dimensional layered material, MXene material has the advantages of high specific surface area and high electrical conductivity, and has potential application value in the field of electrocatalysis. However, two-dimensional MXene sheets are very easy to self-stack, which leads to increased electrode film thickness, decreased electron transport and ion diffusion capabilities, and thus affects its catalytic activity.
[0008] Therefore, how to develop a new catalyst with high catalytic activity and selectivity has become a difficulty and challenge in the current field of synthetic ammonia technology. Summary of the invention
[0009] In order to solve the above problems, the present application provides a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrode and a preparation method thereof.
[0010] In the first aspect, the present application provides a method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst, using the following technical solution: A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst comprises the following steps: Step 1: Preparation of SnO2 quantum dots / MXene materials: Step 1a: Mix 1-8 parts by mass of Mo2CT x MXene is placed in anhydrous ethanol aqueous solution, magnetically stirred and ultrasonically dispersed to obtain uniform Mo2CT x MXene dispersion; Step 1b: Dissolve 4-6 parts by mass of SnCl4·5H2O in an inorganic acid solution, stir magnetically, add 0.5-1.5 parts by mass of urea, and stir; Step 1c: Mo2CT x The MXene dispersion is added to the material in step 1b and stirred; then reacted at 175-185°C for 8-16h; Step 1d: After the reaction in step 1c is completed, the impurities in the obtained precipitate are washed away, and the precipitate is frozen and dried to obtain SnO2 quantum dots / MXene material; Step 2: Place the SnO2 quantum dots / MXene material in anhydrous ethanol and perform magnetic stirring and ultrasonic dispersion until a uniform SnO2 quantum dots / MXene material dispersion is obtained; Step 3: dissolving the inorganic metal salt and the organic ligand in the organic mixed solution, stirring, and dropping the SnO2 quantum dot / MXene material dispersion into the solution during stirring; The molar ratio of inorganic metal salt to organic ligand is 1:(2-4); The organic mixed solution includes one of DMF / CH3OH and DMF / CH3CH2OH; The inorganic metal salt includes one of bismuth nitrate, zinc nitrate, zinc acetate, copper nitrate and copper acetate; The organic ligand includes one of terephthalic acid, 4,4-bipyridine, and dimethylimidazole; Step 4: react the material in step 3 at 140-180° C. for 8-16 hours, collect the powder by centrifugation, wash and dry to obtain a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst.
[0011] As a two-dimensional material with high conductivity, MXene is used as a component of the catalyst, which can significantly improve the conductivity of the overall catalyst. Although the conductivity of MOFs material itself is poor, by compounding with MXene, the excellent conductivity of MXene can be utilized to make it easier for electrons to be transmitted inside the catalyst, thereby improving the catalytic efficiency. The SnO2 quantum dot / MXene material obtained by reaction under specific conditions helps to evenly disperse the SnO2 quantum dots on the surface or between the layers of MXene, avoiding the agglomeration of SnO2 quantum dots. At the same time, the two-dimensional structure of MXene provides more attachment points for SnO2 quantum dots, further reducing the possibility of agglomeration. For the problem of easy self-stacking between MXene sheets, the introduction of SnO2 quantum dots and the growth of MOFs both play a role in inhibiting the self-stacking of MXene sheets. SnO2 quantum dots can fill between MXene sheets, increase the interaction force between the layers, and prevent the stacking of sheets. At the same time, the growth of MOFs will also occupy the space on the surface of MXene sheets, further preventing the close stacking of sheets.
[0012] The specially prepared catalyst contains MOFs, SnO2 quantum dots and MXene with different hydrophilicity and hydrophobicity, which helps to form a hydrophilic-hydrophobic interface inside the catalyst. This interface structure is conducive to the adsorption of reactants and the desorption of products, thereby improving catalytic activity and selectivity.
[0013] Preferably, the inorganic acid solution in step 1b is a HCl solution with a concentration of 0.1-0.3 mol / L.
[0014] Preferably, in step 1d, the precipitate obtained is soaked in water or anhydrous ethanol to wash away impurities, and then the washed product is frozen for 24 hours and then dried in a hot air vacuum.
[0015] Preferably, in the DMF / CH3OH, the volume ratio of DMF and CH3OH is 1:(0.5-2); in the DMF / CH3CH2OH, the volume ratio of DMF and CH3CH2OH is 1:(0.5-2).
[0016] In a second aspect, the present application provides a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst.
[0017] The 2D-0D-2D structure (two-dimensional MOFs, zero-dimensional SnO2 quantum dots and two-dimensional MXene) proposed in this application makes full use of the synergistic effect between the components through reasonable structural design. This structure not only improves the conductivity and stability of the catalyst, but also optimizes the transport path of the reactants and the distribution of catalytic active sites, thereby achieving good catalytic activity and selectivity for the N2 reduction reaction to synthesize ammonia.
[0018] In a third aspect, the present application provides a method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode, using the following technical solution: A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode comprises the following steps: Step A: Pretreatment of electrode substrate: Step A1: ultrasonically treat the carbon paper in deionized ethanol and distilled water respectively; Step A2: soaking the carbon paper treated in step A1 in an acid solution and rinsing it; then soaking it in an alkali solution and rinsing it; and then soaking it in water; Step A3: placing the carbon paper treated in step A2 in a mixed solution of nitric acid and hydrogen peroxide, and ultrasonically treating at 50-70° C. and 80-100 Hz; Step A4: calcining the carbon paper after ultrasonic treatment in step A3 at 400-500°C for 20-40min to obtain an electrode substrate; Step B: adding the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst described in claim 5 to the dispersion and ultrasonically mixing to obtain a 20-30 mg / mL suspension; Step C: evenly drop the suspension onto the surface of the electrode substrate, then apply 0.01-0.1 wt % Nafion solution onto the surface of the electrode substrate, and dry to obtain a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode.
[0019] By adopting the above technical solution, the pretreatment process of the electrode substrate ensures the cleanliness and hydrophilicity of the electrode surface, providing a good foundation for the uniform coating of the catalyst. Through ultrasonic treatment with deionized ethanol and distilled water, as well as soaking and rinsing with acid and alkali solutions, impurities on the surface of carbon paper are effectively removed and its surface properties are improved. The subsequent ultrasonic treatment with a mixed solution of nitric acid and hydrogen peroxide and high-temperature calcination steps further enhance the stability and conductivity of the electrode substrate, providing strong support for the efficient operation of the catalyst.
[0020] Preferably, the dispersion liquid comprises one of methanol and ethanol.
[0021] Preferably, in step A2, the acid solution includes a 0.5-1 mol / L HCl solution; the alkali solution includes a 0.5-1 mol / L NaOH solution.
[0022] Preferably, in the mixed solution, the volume ratio of nitric acid to hydrogen peroxide is 1:(0.8-1.2).
[0023] In a fourth aspect, the present application provides a MOFs / SnO2 quantum dot / MXene catalyst electrode.
[0024] The special structure of the two-dimensional MOFs / SnO2 quantum dot / MXene catalyst can effectively improve the conductivity and stability of the catalyst electrode. The special structure of the catalyst makes the catalytic active sites more fully distributed on the surface of the catalyst electrode. The catalyst electrode can more effectively adsorb and activate nitrogen molecules in the N2 reduction reaction of ammonia synthesis, effectively improving the catalytic activity and selectivity, and can also effectively reduce the reduction potential required for reduction.
[0025] In summary, this application has the following beneficial effects: 1. The two-dimensional MOFs / SnO2 quantum dots / MXene catalyst of the present application realizes a 2D-0D-2D structure (two-dimensional MOFs, zero-dimensional SnO2 quantum dots and two-dimensional MXene) under a reasonable structural design, thereby making full use of the synergistic effect between the components. This structure not only improves the conductivity and stability of the catalyst, but also optimizes the transport path of the reactants and the distribution of catalytic active sites, thereby achieving good catalytic activity and selectivity for the N2 reduction reaction of ammonia synthesis.
[0026] 2. The MOFs / SnO2 quantum dot / MXene catalyst electrode provided in the present application can overcome the problems of low catalytic activity, excessively high reaction overpotential, poor solubility of N2 in aqueous solution, slow diffusion rate, and low activation efficiency of N2 in existing electrocatalytic N2 reduction methods, and realize efficient nitrogen reduction to synthesize ammonia at room temperature and pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the SEM image of the two-dimensional Bi-BDC / SnO2 quantum dots / MXene catalyst prepared in Example 1.
[0028] Figure 2 This is the LSV curve of the two-dimensional Bi-BDC / SnO2 quantum dot / MXene catalyst electrode prepared in Example 1 in Ar and N2 atmospheres.
[0029] Figure 3This is a graph of ammonia yield and Faraday efficiency of the two-dimensional Bi-BDC / SnO2 quantum dot / MXene catalyst electrode prepared in Example 1 at different reduction potentials.
[0030] Figure 4 It is a performance comparison chart of the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrodes prepared in Examples 1-3 and the SnO2 quantum dots / MXene catalyst electrodes of Comparative Example 1. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0032] The raw materials used in the following examples and comparative examples are all commercially available products.
[0033] Preparation Example Preparation Example 1 Mo2CT x Preparation of MXene: Mo2CT was prepared according to the literature (Chemical Engineering Journal, 2021, 410, 128349) x MXene materials, specifically: 1.0 g of Mo2Ga2C was weighed and placed in a 50 mL mixed solution of hydrofluoric acid (mass fraction 49%) and concentrated hydrochloric acid with a volume ratio of 3:2. The mixture was stirred at 35 °C for 72 hours to peel off the layered Mo2CTx MXene. After etching, the obtained solid was centrifuged, thoroughly rinsed with distilled water and ethanol, and then vacuum dried at 60 °C to obtain the target product Mo2CTx MXene. Example
[0034] Example 1 A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode comprises the following steps: Step 1: Preparation of 2D MOFs / SnO2 quantum dots / MXene catalyst Step 1: Preparation of SnO2 quantum dots / MXene materials: Step 1a: 300 mg of Mo2CT prepared in Preparation Example 1 x MXene was placed in 10 mL of anhydrous ethanol aqueous solution, magnetically stirred for 1 h, and ultrasonically dispersed for 30 min, which was repeated three times to obtain a uniform Mo2CT x MXene dispersion.
[0035] Step 1b: Dissolve 0.526 g SnCl4·5H2O in 30 mL 0.1 mol / L hydrochloric acid solution and stir magnetically for 30 minutes. Add 0.1 g urea and stir for 1 hour.
[0036] Step 1c: Mo2CT x The MXene dispersion was added to the material in step 1b, stirred thoroughly for 1 h, transferred into a polytetrafluoroethylene-lined autoclave, and reacted at 180 °C for 12 h.
[0037] Step 1d: Cool naturally, soak the obtained precipitate in deionized water and anhydrous ethanol and stir for 30 minutes respectively, repeat 3 times, freeze the obtained product for 24 hours, and then vacuum dry it at 60°C for 24 hours to obtain SnO2 quantum dots / MXene material.
[0038] Step 2: Place the SnO2 quantum dots / MXene material in 20 mL of anhydrous ethanol, stir magnetically for 10 min, and ultrasonicate for 30 min. Repeat this process more than three times until a uniform SnO2 quantum dots / MXene material dispersion is obtained.
[0039] Step 3: Dissolve Bi(NO3)3·5H2O (1 mmol) and terephthalic acid (3 mmol) in a 1:3 molar ratio in 30 mL of a 1:2 DMF / CH3OH mixed solution, stir at room temperature for 30 min, and then add the uniformly prepared SnO2 quantum dots / Mo2CT dropwise while stirring. x MXene material dispersion was dripped in 30 minutes.
[0040] Step 4: Transfer the material from step 3 to a 100 mL polytetrafluoroethylene-lined reactor, react at 160° C. for 12 h, collect the resulting powder by centrifugation, and wash with ethanol.
[0041] Then, it was dried in a vacuum oven at 60 °C for 12 h to obtain a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst, specifically a two-dimensional Bi-BDC / SnO2 quantum dots / Mo2CT x Mxene catalyst.
[0042] SEM image of two-dimensional Bi-BDC / SnO2 quantum dots / MXene catalyst reference Figure 1 It can be seen from the figure that the prepared catalyst has a two-dimensional layer structure.
[0043] Step 2: Preparation of catalyst electrode Step A: Pretreatment of electrode substrate: Step A1: Cut the carbon paper into a suitable size, and then ultrasonically treat the carbon paper in deionized ethanol and distilled water at room temperature for 20 minutes respectively.
[0044] Step A2: Soak the carbon paper treated in step A1 in 50 mL of 0.5 mol / L HCl for 2 h, and then rinse.
[0045] Then, the samples were immersed in 50 mL of 0.5 mol / L NaOH for 2 h and then rinsed with deionized water.
[0046] Then soak in deionized water for 5 h.
[0047] Step A3: Place the carbon paper treated in step A2 in a mixed solution of nitric acid and hydrogen peroxide in a volume ratio of 1:1, and ultrasonicate at 60° C. and 90 Hz for 30 minutes.
[0048] Step A4: The carbon paper after ultrasonic treatment in step A3 was calcined at 450° C. for 30 minutes.
[0049] The taken out calcined product was rinsed with deionized water to a pH of 7 and dried at 120° C. for 12 h to obtain an electrode matrix.
[0050] Step B: Add 10 mg of the two-dimensional Bi-BDC / SnO2 quantum dots / MXene catalyst prepared in step 1 to 400 μL of ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension of 25 mg / mL.
[0051] Step C: Use a 100μL pipette to draw 100μL of the suspension and evenly apply it on the surface of the electrode substrate, once on the front and back sides.
[0052] Afterwards, 100 μL of Nafion solution (0.05 wt%) was evenly drop-coated on the surface and dried to obtain a two-dimensional Bi-BDC / SnO2 quantum dot / MXene catalyst electrode.
[0053] Example 2 A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode is different from that in Example 1 in that some raw materials and parameters are different, as follows: Step 1: Preparation of 2D MOFs / SnO2 quantum dots / MXene catalyst Step 1: Preparation of SnO2 quantum dots / MXene materials: Step 1a: 800 mg of Mo2CT prepared in Preparation Example 1 x MXene was placed in 10 mL of anhydrous ethanol aqueous solution, magnetically stirred for 1 h, and ultrasonically dispersed for 30 min, which was repeated three times to obtain a uniform Mo2CT x MXene dispersion.
[0054] Step 1b: Dissolve 0.4 g SnCl4·5H2O in 30 mL 0.3 mol / L hydrochloric acid solution and stir magnetically for 30 minutes. Add 0.05 g urea and stir for 1 hour.
[0055] Step 1c: Mo2CT x The MXene dispersion was added to the material in step 1b, stirred thoroughly for 1 h, transferred into a polytetrafluoroethylene-lined autoclave, and reacted at 175 °C for 16 h.
[0056] Step 1d: Cool naturally, soak the obtained precipitate in deionized water and anhydrous ethanol and stir for 30 minutes respectively, repeat 3 times, freeze the obtained product for 24 hours, and then vacuum dry it at 60°C for 24 hours to obtain SnO2 quantum dots / MXene material.
[0057] Step 2: Place the SnO2 quantum dots / MXene material in 20 mL of anhydrous ethanol, stir magnetically for 10 min, and ultrasonicate for 30 min. Repeat this process more than three times until a uniform SnO2 quantum dots / MXene material dispersion is obtained.
[0058] Step 3: Dissolve Zn(NO3)2·6H2O (1 mmol) and terephthalic acid (2 mmol) in a molar ratio of 1:2 in 30 mL of a DMF / CH3CH2OH mixture with a volume ratio of 1:0.5, stir at room temperature for 30 min, and then add the uniformly prepared SnO2 quantum dots / Mo2CT dropwise while stirring. x MXene material dispersion was dripped in 30 minutes.
[0059] Step 4: Transfer the material from step 3 to a 100 mL polytetrafluoroethylene-lined reactor, react at 140° C. for 16 h, collect the resulting powder by centrifugation, and wash with ethanol.
[0060] Then, the catalyst was dried in a vacuum oven at 60 °C for 12 h to obtain a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst, specifically a two-dimensional Zn-BDC / SnO2 quantum dots / Mo2CT x Mxene catalyst.
[0061] Step 2: Preparation of catalyst electrode Step A: Pretreatment of electrode substrate: Step A1: Cut the carbon paper into a suitable size, and then ultrasonically treat the carbon paper in deionized ethanol and distilled water at room temperature for 20 minutes respectively.
[0062] Step A2: Soak the carbon paper treated in step A1 in 50 mL 1 mol / L HCl for 2 h, and then rinse.
[0063] Then, the samples were immersed in 50 mL 1 mol / L NaOH for 2 h and then rinsed with deionized water.
[0064] Then soak in deionized water for 5 h.
[0065] Step A3: Place the carbon paper treated in step A2 in a mixed solution of nitric acid and hydrogen peroxide in a volume ratio of 1:0.8, and ultrasonicate at 50° C. and 100 Hz for 30 minutes.
[0066] Step A4: The carbon paper after ultrasonic treatment in step A3 was calcined at 400° C. for 40 minutes.
[0067] The taken out calcined product was rinsed with deionized water to a pH of 7 and dried at 120° C. for 12 h to obtain an electrode matrix.
[0068] Step B: Add 8 mg of the two-dimensional Zn-BDC / SnO2 quantum dots / MXene catalyst prepared in step 1 to 400 μL of ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension of 20 mg / mL.
[0069] Step C: Use a 100μL pipette to draw 100μL of the suspension and evenly apply it on the surface of the electrode substrate, once on the front and back sides.
[0070] Afterwards, 100 μL of Nafion solution (0.01 wt%) was evenly drop-coated on the surface and dried to obtain a two-dimensional Zn-BDC / SnO2 quantum dot / MXene catalyst electrode.
[0071] Example 3 A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode is different from that in Example 1 in that some raw materials and parameters are different, as follows: Step 1: Preparation of 2D MOFs / SnO2 quantum dots / MXene catalyst Step 1: Preparation of SnO2 quantum dots / MXene materials: Step 1a: 200 mg of Mo2CT prepared in Preparation Example 1 x MXene was placed in 10 mL of anhydrous ethanol aqueous solution, magnetically stirred for 1 h, and ultrasonically dispersed for 30 min, which was repeated three times to obtain a uniform Mo2CT x MXene dispersion.
[0072] Step 1b: Dissolve 0.6 g SnCl4·5H2O in 30 mL 0.1 mol / L hydrochloric acid solution and stir magnetically for 30 minutes. Add 0.15 g urea and stir for 1 hour.
[0073] Step 1c: Mo2CT xThe MXene dispersion was added to the material in step 1b, stirred thoroughly for 1 h, transferred into a polytetrafluoroethylene-lined autoclave, and reacted at 185 °C for 8 h.
[0074] Step 1d: Cool naturally, soak the obtained precipitate in deionized water and anhydrous ethanol and stir for 30 minutes respectively, repeat 3 times, freeze the obtained product for 24 hours, and then vacuum dry it at 60°C for 24 hours to obtain SnO2 quantum dots / MXene material.
[0075] Step 2: Place the SnO2 quantum dots / MXene material in 20 mL of anhydrous ethanol, stir magnetically for 10 min, and ultrasonicate for 30 min. Repeat this process more than three times until a uniform SnO2 quantum dots / MXene material dispersion is obtained.
[0076] Step 3: Dissolve Zn(CH3COO)2 (1 mmol) and 4,4-bipyridine (4 mmol) in a molar ratio of 1:4 in 30 mL of a DMF / CH3OH mixture with a volume ratio of 1:1, stir at room temperature for 30 min, and then add the uniformly prepared SnO2 quantum dots / Mo2CT dropwise while stirring. x MXene material dispersion was dripped in 30 minutes.
[0077] Step 4: Transfer the material from step 3 to a 100 mL polytetrafluoroethylene-lined reactor, react at 180° C. for 8 h, collect the resulting powder by centrifugation, and wash with ethanol.
[0078] Then, the catalyst was dried in a vacuum oven at 60 °C for 12 h to obtain a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst, specifically a two-dimensional Zn-(4,4,-Bpy) / SnO2 quantum dots / Mo2CT x Mxene catalyst.
[0079] Step 2: Preparation of catalyst electrode Step A: Pretreatment of electrode substrate: Step A1: Cut the carbon paper into a suitable size, and then ultrasonically treat the carbon paper in deionized ethanol and distilled water at room temperature for 20 minutes respectively.
[0080] Step A2: Soak the carbon paper treated in step A1 in 50 mL of 0.5 mol / L HCl for 2 h, and then rinse.
[0081] Then, the samples were immersed in 50 mL of 0.5 mol / L NaOH for 2 h and then rinsed with deionized water.
[0082] Then soak in deionized water for 5 h.
[0083] Step A3: Place the carbon paper treated in step A2 in a mixed solution of nitric acid and hydrogen peroxide in a volume ratio of 1:1.2, and ultrasonicate at 70° C. and 80 Hz for 30 minutes.
[0084] Step A4: calcining the carbon paper after ultrasonic treatment in step A3 at 500° C. for 20 minutes.
[0085] The taken out calcined product was rinsed with deionized water to a pH of 7 and dried at 120° C. for 12 h to obtain an electrode matrix.
[0086] Step B: Add 12 mg of the two-dimensional Zn-(4,4,-Bpy) / SnO2 quantum dots / MXene catalyst prepared in step 1 to 400 μL of ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension of 30 mg / mL.
[0087] Step C: Use a 100μL pipette to draw 100μL of the suspension and evenly apply it on the surface of the electrode substrate, once on the front and back sides.
[0088] Afterwards, 100 μL of Nafion solution (0.1 wt%) was evenly dripped on the surface and dried to obtain a two-dimensional Zn-(4,4,-Bpy) / SnO2 quantum dot / MXene catalyst electrode.
[0089] Comparative Example Comparative Example 1 A method for preparing a SnO2 quantum dot / MXene catalyst electrode comprises the following steps: Step 1: Preparation of SnO2 quantum dots / MXene materials: Step 1a: 300 mg of Mo2CT prepared in Preparation Example 1 x MXene was placed in 10 mL of anhydrous ethanol aqueous solution, magnetically stirred for 1 h, and ultrasonically dispersed for 30 min, which was repeated three times to obtain a uniform Mo2CT x MXene dispersion.
[0090] Step 1b: Dissolve 0.526 g SnCl4·5H2O in 30 mL 0.1 mol / L hydrochloric acid solution and stir magnetically for 30 minutes. Add 0.1 g urea and stir for 1 hour.
[0091] Step 1c: Mo2CT x The MXene dispersion was added to the material in step 1b, stirred thoroughly for 1 h, transferred into a polytetrafluoroethylene-lined autoclave, and reacted at 180 °C for 12 h.
[0092] Step 1d: Cool naturally, soak the obtained precipitate in deionized water and anhydrous ethanol and stir for 30 minutes respectively, repeat 3 times, freeze the obtained product for 24 hours, and then vacuum dry it at 60°C for 24 hours to obtain SnO2 quantum dots / MXene material.
[0093] Step 2: Preparation of catalyst electrode Step A: Pretreatment of electrode substrate: Step A1: Cut the carbon paper into a suitable size, and then ultrasonically treat the carbon paper in deionized ethanol and distilled water at room temperature for 20 minutes respectively.
[0094] Step A2: Soak the carbon paper treated in step A1 in 50 mL of 0.5 mol / L HCl for 2 h, and then rinse.
[0095] Then, the samples were immersed in 50 mL of 0.5 mol / L NaOH for 2 h and then rinsed with deionized water.
[0096] Then soak in deionized water for 5 h.
[0097] Step A3: Place the carbon paper treated in step A2 in a mixed solution of nitric acid and hydrogen peroxide in a volume ratio of 1:1, and ultrasonicate at 60° C. and 90 Hz for 30 minutes.
[0098] Step A4: The carbon paper after ultrasonic treatment in step A3 was calcined at 450° C. for 30 minutes.
[0099] The taken out calcined product was rinsed with deionized water to a pH of 7 and dried at 120° C. for 12 h to obtain an electrode matrix.
[0100] Step B: Add 10 mg of the SnO2 quantum dots / MXene material prepared in step 1 to 400 μL of ethanol, and ultrasonicate for 30 min to obtain a uniformly mixed suspension of 25 mg / mL.
[0101] Step C: Use a 100μL pipette to draw 100μL of the suspension and evenly apply it on the surface of the electrode substrate, once on the front and back sides.
[0102] Afterwards, 100 μL of Nafion solution (0.05 wt%) was evenly dripped on the surface and dried to obtain a SnO2 quantum dot / MXene catalyst electrode.
[0103] Performance testing The two-dimensional Bi-BDC / SnO2 quantum dot / MXene catalyst electrode of Example 1 was used as the working electrode, and an H-type electrolytic cell with a cation diaphragm was selected. 60 mL of 0.1 mol / L NaSO4 electrolyte was added to each of the cathode and anode chambers, and N2 gas was introduced into the cathode chamber at a rate of 5 mL / s for 30 min. The electrocatalytic performance of the catalyst electrode of Example 1 was tested at a potential window of (-0.8)-0 V. Finally, the cathode electrolyte after the 2h It test was tested by the nanometer reagent method using an ultraviolet spectrophotometer to determine the ammonia yield and FE of the catalyst.
[0104] LSV curves of two-dimensional Bi-BDC / SnO2 quantum dots / MXene catalyst electrode in Ar (same as the above N2 test method except different gas) and N2 atmospheres Figure 2 .
[0105] according to Figure 2 It can be seen that the reduction current density in N2 atmosphere is significantly higher than that in Ar, indicating that the material has good selectivity for N2 reduction reaction.
[0106] Ammonia yield and FE results are detailed in Figure 3 , and are summarized in Table 1.
[0107] Table 1 According to the test data, at -0.2V, the Faraday efficiency can reach up to 37.80%, and at -0.5V, the ammonia yield is up to 16.67μg·h -1 mg -1 , indicating that the material has a good catalytic effect on N2 reduction reaction.
[0108] The above method was used to detect the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrodes of Examples 2-3 and the SnO2 quantum dots / MXene catalyst electrodes of Comparative Example 1, and the electrocatalytic performance of different catalysts was tested at a reduction potential of -0.5 V vs RHE.
[0109] The results are shown in Figure 4 , and are summarized in Table 2.
[0110] Table 2 Group Code <![CDATA[Ammonia production rate (μg·h -1 mg -1 )]]> FE(%) Example 1 Catalyst 3 16.67 24.10 Example 2 Catalyst 2 14.46 20.09 Example 3 Catalyst 4 15.02 21.43 Comparative Example 1 Catalyst 1 5.91 10.51 According to the test data, it can be seen that the catalytic performance of catalysts 2-4 is significantly higher than that of catalyst 1, and the catalytic performance of catalyst 3 (Example 1) is the best.
[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst, characterized in that: The following steps are involved: Step 1: Preparation of SnO2 quantum dots / MXene materials: Step 1a: Mix 1-8 parts by mass of Mo2CT x MXene is placed in anhydrous ethanol aqueous solution, magnetically stirred and ultrasonically dispersed to obtain uniform Mo2CT x MXene dispersion; Step 1b: Dissolve 4-6 parts by mass of SnCl4·5H2O in an inorganic acid solution, stir magnetically, add 0.5-1.5 parts by mass of urea, and stir; Step 1c: Mo2CT x The MXene dispersion is added to the material in step 1b and stirred; then reacted at 175-185°C for 8-16h; Step 1d: After the reaction in step 1c is completed, the impurities in the obtained precipitate are washed away, and the precipitate is frozen and dried to obtain SnO2 quantum dots / MXene material; Step 2: Place the SnO2 quantum dots / MXene material in anhydrous ethanol and perform magnetic stirring and ultrasonic dispersion until a uniform SnO2 quantum dots / MXene material dispersion is obtained; Step 3: dissolving the inorganic metal salt and the organic ligand in the organic mixed solution, stirring, and dropping the SnO2 quantum dot / MXene material dispersion into the solution during stirring; The molar ratio of inorganic metal salt to organic ligand is 1:(2-4); The organic mixed solution includes one of DMF / CH3OH and DMF / CH3CH2OH; The inorganic metal salt includes one of bismuth nitrate, zinc nitrate, zinc acetate, copper nitrate and copper acetate; The organic ligand includes one of terephthalic acid, 4,4-bipyridine, and dimethylimidazole; Step 4: react the material in step 3 at 140-180° C. for 8-16 hours, collect the powder by centrifugation, wash and dry to obtain a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst.
2. The method for preparing the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst according to claim 1, characterized in that: The inorganic acid solution in step 1b is a HCl solution with a concentration of 0.1-0.3 mol / L.
3. The method for preparing the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst according to claim 1, characterized in that: In the step 1d, the obtained precipitate is soaked in water or anhydrous ethanol to wash away impurities, and then the washed product is frozen and dried.
4. The method for preparing the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst according to claim 1, characterized in that: In the DMF / CH3OH, the volume ratio of DMF to CH3OH is 1:(0.5-2); in the DMF / CH3CH2OH, the volume ratio of DMF to CH3CH2OH is 1:(0.5-2).
5. A two-dimensional MOFs / SnO2 quantum dots / MXene catalyst prepared by the preparation method of the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst according to claims 1-4.
6. A method for preparing a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode, characterized in that: The following steps are involved: Step A: Pretreatment of electrode substrate: Step A1: ultrasonically treat the carbon paper in deionized ethanol and distilled water respectively; Step A2: soaking the carbon paper treated in step A1 in an acid solution and rinsing it; then soaking it in an alkali solution and rinsing it; and then soaking it in water; Step A3: placing the carbon paper treated in step A2 in a mixed solution of nitric acid and hydrogen peroxide, and ultrasonically treating at 50-70° C. and 80-100 Hz; Step A4: calcining the carbon paper after ultrasonic treatment in step A3 at 400-500° C. for 20-40 min to obtain an electrode substrate; Step B: adding the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst described in claim 5 to the dispersion and ultrasonically mixing to obtain a suspension of 20-30 mg / mL; Step C: Evenly drop the suspension onto the surface of the electrode substrate, then apply 0.01-0.1wt% Nafion solution onto the surface of the electrode substrate and dry it to obtain a two-dimensional MOFs / SnO2 quantum dot / MXene catalyst electrode.
7. The method for preparing a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrode according to claim 6, characterized in that: The dispersion liquid includes one of methanol and ethanol.
8. The method for preparing a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrode according to claim 6, characterized in that: In the step A2, the acid solution includes a 0.5-1 mol / L HCl solution; the alkali solution includes a 0.5-1 mol / L NaOH solution.
9. The method for preparing a two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrode according to claim 6, characterized in that: In the mixed solution, the volume ratio of nitric acid to hydrogen peroxide is 1:(0.8-1.2).
10. A two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrode prepared by the preparation method of the two-dimensional MOFs / SnO2 quantum dots / MXene catalyst electrode according to any one of claims 6 to 9.
Citation Information
Patent Citations
Oxygen evolution reaction (OER) catalyst based on composite structure of MXene and metal-organic frameworks (MOFs) and synthesis method of catalyst
CN110038634A
Preparation and application of monatomic platinum catalyst based on MXene quantum dots
CN112264062A
Three-dimensional structure MXene / SnO2 / C negative electrode composite material and preparation method thereof
CN114039051A
Electrostatic self-assembled SnO2-coated NDPC / MXene nano composite material as well as preparation method and application thereof
CN114613952A
Preparation method and application of MXene-based sodium metal negative electrode composite material with nano confinement effect
CN115528234A